Could Fingolimod Combined with Bevacizumab Be a New Hope in Glioblastoma Treatment? - Murat Baloglu; Canan Vejselova Sezer; Hüseyin Izgördü; Ibrahim Yilmaz; Hatice Mehtap Kutlu (Current Issues in Molecular Biology, 2025)
Glioblastoma, classified as a grade IV astrocytoma, is an aggressive and malignant primary brain tumor with no known cure. Despite the implementation of standard medical and surgical treatment protocols, the disease often progresses with unsatisfactory outcomes. This study aimed to evaluate the cytotoxic, proapoptotic, and antimetastatic effects of anti-angiogenic monoclonal antibody bevacizumab combined with the sphingosine-1-phosphate receptor modulator fingolimod on rat glioma C6 cells. The cytotoxicity of bevacizumab and fingolimod was evaluated using the MTT assay. Proapoptotic activity was assessed through flow cytometric analyses, including Annexin V–FITC staining, caspase 3/7 activation, and mitochondrial membrane potential measurements. Morphological changes were examined using confocal microscopy. Antimetastatic effects were evaluated via anti-migration and colony formation assays. The combination of bevacizumab and fingolimod exhibited antiproliferative, cytotoxic, proapoptotic, and antimetastatic effects on C6 glioma cells at low IC50 concentrations. Based on growth inhibitory, proapoptotic, and antimetastatic activities on C6 glioma cells, the combination of bevacizumab and fingolimod demonstrates significant growth-inhibitory, proapoptotic, and antimetastatic activities against C6 glioma cells, suggesting its potential as a promising pharmacotherapeutic approach for the treatment of glioblastoma.